Unmanned system for terrain reconnaissance - Lee, Jansen Chang Sheng (2015)
In present times with the usage of quadcopters as drones has increased drastically with the advancement of flight boards and sensors to produce more stable flights. This has allowed consumers to quickly grasp the ways of flying and manoeuvring. The purpose of this project is to explore the usage of a multi system surveillance quadcopter drone for usage in urban surveillance. The quadcopter uses a NAZA MV2 flight computer transferred from a DJI Phantom 1 Ready to fly (RTF) quadcopter onto a frame to allow for modifications. Extensive testing was done via frequent flights with each individual modification prior to flying and eventually flight with all modifications on board garnered positive results. Troubleshooting involved distribution of weight and calibration of the flight sensors. Presently, the quadcopter is able to achieve autonomous outdoor flight both day and night along with its payload consisting of the various modifications done to it. This document charts the building of this quad and its modifications and the testing procedures leading up to its completion. The main aims were met in this project resulting in a cheaper alternative to most surveillance drones sold by companies specialising in such drones.